A study of standard tender documents (goods) of PPR 2008 under un procurement manual - Mahmud, Md. Hasibul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.